2015
DOI: 10.1134/s1022795415070145
|View full text |Cite
|
Sign up to set email alerts
|

Allelic composition in the Vrn-A1, Vrn-B1, and Vrn-B3 genes of double haploid lines of hexaploid triticale

Abstract: Vernalization genes are associated with the adaptation capability, heading dates, and yield poten tial of grain crops. The allelic composition in the Vrn A1, Vrn B1, and Vrn B3 genes was defined in 42 lines of double haploids of hexaploid triticale, which were produced through in vitro anther culture. Two alleles (Vrn A1a and vrn A1) were found at the Vrn A1 locus and three alleles (Vrn B1a, Vrn B1c, and vrn B1) were found at the Vrn B1 locus. All double haploids carried the recessive allele at the Vrn B3 locu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 25 publications
0
1
0
1
Order By: Relevance
“…Vernalisation and Photoperiod genes are key factors of wheat development and some works have demonstrated that they may determine not only heading and flowering times but maturity time as well ( Shcherban, Emtseva & Efremova, 2012 ; Kamran et al, 2013 ; Zaitseva & Lemesh, 2015 ; Whittal et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…Vernalisation and Photoperiod genes are key factors of wheat development and some works have demonstrated that they may determine not only heading and flowering times but maturity time as well ( Shcherban, Emtseva & Efremova, 2012 ; Kamran et al, 2013 ; Zaitseva & Lemesh, 2015 ; Whittal et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…Возможно, ген Eps, определяющий скороспелость per se, является блоком полигенов (модификаторов) с малым эффектом, который идентифицируется методами генетического анализа. Разная скорость развития растений мягкой пшеницы и признаки продуктивности могут ассоциироваться с определенным сочетанием аллелей генов Ppd и Vrn (Potokina et al, 2012;Zaitseva, Lemesh, 2015).…”
Section: Introductionunclassified